A mindful approach to physician self-care - Janine M. Kirby; Peter D. Milligan; Hofmeyr H. Conradie; Belinda M. McIntosh (South African Family Practice)
There has been an increasing awareness of the importance of physician mental health. Several South African studies show a high prevalence of burnout among doctors. Burnout is characterised by three components: exhaustion, depersonalisation, and a sense of a lack of efficacy. Burnout is a result of both external and internal pressures. While lifestyle modification is essential, mindfulness-informed programmes promote self-regulation and resilience. Mindfulness programmes comprise three components: present moment awareness, perspective-taking and wisdom, and compassion. Physician wellness begins with individuals recognising the need of self-care and giving themselves permission to prioritise this. Ongoing identification of self-care needs and acting compassionately to address these needs is essential.